2021
DOI: 10.1111/jpn.13557
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and nutritional characteristics of Cannabis sativa L. co‐products

Abstract: Hemp is a dicotyledonous plant from the family of Cannabaceae, genus Cannabis, and is considered one of the oldest domesticated crops. For several years, this plant was used for different purposes, such as clothing and shoes, cordages, carpets and tarps, maritime ropes, sails and nets, and paper production (Crini et al., 2020).However, in the last century, hemp cultivation was decreased due

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 45 publications
5
19
0
Order By: Relevance
“…For this purpose, the in vitro gas production technique (IVGPT) was applied. The IVGPT reproduces at the laboratory scale the feed degradation occurring in the rumen and studies the fermentation kinetics, also estimating its nutritional value [ 46 ]. The organic matter degradability (OMD) and gas produced after 120 h of incubation (OMCV and A) showed lower values for all the beech-based diet samples, except Fs/3/2 at the 200-mg dose level, than the control diet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, the in vitro gas production technique (IVGPT) was applied. The IVGPT reproduces at the laboratory scale the feed degradation occurring in the rumen and studies the fermentation kinetics, also estimating its nutritional value [ 46 ]. The organic matter degradability (OMD) and gas produced after 120 h of incubation (OMCV and A) showed lower values for all the beech-based diet samples, except Fs/3/2 at the 200-mg dose level, than the control diet.…”
Section: Resultsmentioning
confidence: 99%
“…Beech Fs/1/1 extract and its Fs/2/1 and Fs/3/2 fractions were incubated at 0 (control), 50, and 200-mg dose levels with one gram of a diet composed by mixed hay, corn silage, and concentrate (crude protein: 15.0%, NDF: 46.0%) in hermetically sealed serum flasks (120 mL each, three replications for each treatment) with buffered rumen fluid (10 mL) at 39 °C under anaerobic conditions [ 46 ]. The rumen liquor was collected at a slaughterhouse [ 69 ] from four buffalos fed a total mixed ratio.…”
Section: Methodsmentioning
confidence: 99%
“…These authors indicated that the application of safflower and hemp seeds reduced the level of methanogenic bacteria. In a previous study, Vastolo et al [ 46 ] observed a lower amount of gas production after incubating hemp co-products with buffalo ruminal inoculum. These results suggest that the fatty acid profile of hemp could affect the ruminal microbial population.…”
Section: Discussionmentioning
confidence: 99%
“…It might also be possible to assume that these results may have been caused by the presence of secondary compounds in hemp. Indeed, Cannabis sativa plants and co-products contain a multitude of chemicals, including phytocannabinoids, terpenoids, flavonoids, and sterols [ 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro gas production has been used to predict the rumen degradability and metabolizable energy of different animal feeds ( 40 ). A strong correlation between nutritional content and in vitro cumulative gas production exists, and these parameters have gained wide acceptance in the nutritional evaluation of animal feeds ( 41 – 43 ). In vitro gas production is highly dependent on the availability of soluble fractions, which favor ruminal fermentation at the early fermentation stages ( 44 ).…”
Section: Discussionmentioning
confidence: 99%